PENGARUH KEPATUHAN PERAWAT MELAKUKAN CUCI TANGAN SEBELUM PEMASANGAN INFUS TERHADAP KEJADIAN PHLEBITIS - Suratun Suratun; Gustina Gustina; Sunardi Sunardi (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
The hands-washing is a baseline procedure to prevent one of nosocomial infections suchas phlebitis. Nurses have a major role towards Phlebitis’ incidents because they alwaysinteract with their patients for 24 hours. The aim of this research was determine theinfluence of nurses’ compliance to perform hands-washing before inserting IV cathetertowards Phlebitis’ incidents. This research was using Descriptive Correlation designwith Cross Sectional approach. The numbers of sample were 111 nurses and 111admitted patients which were chosen by proportional stratified random samplingtechnique. The data collections were using questionnaires and observational forms. Thebivariate analysis was using Chi Square. The results of this research showed that there isno significant correlation between nurses’ characteristics with phlebitis’ incidents.Similarly, there is no significant correlation between nurses’ compliance to performhands-washing before inserting IV catheter with phlebitis’ incidents. Meanwhile, there isa significant correlation among the availability of hands-washing facilities withphlebitis’ incidents with p value = 0.000. The multivariate analysis was using multiplelogistic regression which showed that the availability of hands-washing facilities is themost dominant factor to decrease the numbers of phlebitis’ incidents with Odd Ratio19.333.